Stuttering severity and responses to social-communicative challenge in preschool-age children who stutter. (September 2014) - Kazenski, Danra; Guitar, Barry; McCauley, Rebecca; Falls, William; Dutko, Lindsay Stallings
Abstract : Purpose: This study assessed indices of autonomic arousal and vocal tension during challenge in preschool-age children who do stutter (CWS) and do not stutter (CWNS). Method: Participants were preschool-age CWS ( n  = 10) and gender- and age-matched CWNS ( n  = 10) who performed in two speaking conditions: (1) 'low' challenge – naming age-appropriate pictures in a familiar room with the same examiner who administered his/her speech-language prescreening test (2) 'high' challenge – recalling the pictures named in condition (1) in a different room with an unfamiliar examiner while wearing acoustic startle electrodes on his/her face. Immediately following the 'high' challenge speaking task, the participants' acoustic startle eyeblink response (ASEB) was measured. Dependent variables were ASEB in the 'high' challenge condition and the acoustic measure of mean fundamental frequency ( F o ) in both challenge conditions. Results: Findings indicated no significant between-group (CWS vs. CWNS) differences in F o or ASEB responses. However, CWS-severe ( n  = 5), when compared with CWS-mild/moderate ( n  = 5), exhibited a statistically significant increase in F o in the 'high' challenge relative to the 'low' challenge condition. Conclusions: Results were taken to suggest that preschool-age CWS-severe exhibit vocal tension while speaking in conditions of social (e.g. speaking to unfamiliar examiner) and communicative (e.g. recalling from memory names of pictures previously shown) challenge, and such vocal behavior is possibly associated with this subgroup's difficulty establishing normally fluent speech.